Pilot project on Global Youth Reproductive Health Program: Implementation in Denpasar City - I Gusti Ayu Agung Putri Krismayanthi; Pande Putu Januraga; Desak Putu Yuli Kurniati (Universitas Udayana, 2019)
Background and purpose: Premarital sexual relations in adolescents and early marriage tends to increase in Indonesia. One of the programs implemented in Indonesia to reduce these problems is the reproductive health program for adolescents in schools. The Youth World Spirit Module or called SEmangaT duniA RemajA (SETARA) is used as a tool for teaching and learning activities in pilot projects in several cities in Indonesia, including Denpasar. This study aims to determine the implementation of the program in Denpasar. Methods: This study employed a qualitative approach conducted at junior high schools in Denpasar City. Data collection was carried out with six focus group discussions (FGDs) consisting of three FGDs with 20 students aged 13-15 years and three FGDs with 15 teachers who were appointed as a facilitator of the program. In addition, indepth interviews were also conducted with three junior high school principals. FGDs and in-depth interviews were recorded, transcribed and analysed thematically using the Miles and Huberman Technique. Results: The study showed that the provision of the SETARA module was able to change the impression of taboo and broaden adolescent insights on reproductive health material. The implementation of this module is slightly different between schools due to differences in time allocation, number of activities in schools and the absence of standardised implementation guidelines. However, teachers and schools continue to support the implementation of this module. Conclusion: This module is quite effective in providing information so as to eliminate the taboo impression from reproductive health material.